Phytochemical and Synergism of Plant and Microbial Insecticides to Eliminate Earias Vittella Gut Epithelial Cells: Life Sciences-Agrochemistry - Ramasamy, Villavan; Natesan, Kanagaraju; Pari, Madhiyazhagan (International Journal of Life Science and Pharma Research, 2022)
The spotted bollwom, Earias vittella is a very serious and polyphagous pest that attacks many plants of Malvaceae family. Such as Lady’s finger (Abelmoschus esculentus Moench), which attacks growing points of the plant. The intensive use of highly toxic and broad-spectrum pesticides threatens the sustainability of vegetable production, mainly due to the development of pest resistance. Consequently, it becomes more difficult to manage key pests and secondary pests, which assume major status due to the elimination of natural enemies from the eco system. In the present study, evaluation of the larvicidal, quantitative food utilization and histological activity of Manihot esculenta, Azadirachtin (AZA), Bacillus thuringiensis var. kurstaki (Btk), and synergistic effects, was carried out against Earias vittella. The GC-MS analysis of M. esculenta was estimated and seventeen different phytoactive compounds were identified. Larvicidal activity of M. esculenta, AZA, and Btk provided significant mortality against E. vittella. The lowest LC50 of individual treatment was from AZA, the LC50 being as follows: 0.122%, 0.131%, 0.150%, 0.157%, and 0.168%, and the LC50 of synergistic treatment was 1.434ppm, 1.469ppm, 1.531ppm, 1.701ppm, and 1.908ppm for I, II, III, IV, and V instars, respectively. The food utilization result showed that, the food intake of E. vittella was significantly reduced after the treatment. Here, synergistic effects controls the food intake, which is highly reduced, and fecal pallet egestion considerably reduces the amount of food consumed. Histological studies state that, after the treatment, the gut of E. vittella is drastically damaged by the biopesticides. M. esculenta, AZA and Btk and their synergism are very effective against the immature stage of E. vittella. Gut region of the insect finely eradicated by the biopesticide. Overall, this study concludes that the taken botanical insecticides are ecofriendly, harmless to mammals and other non-target animals.